Effect of Massage Therapy on Chest Pain, Anxiety, and Stress Among Patients With Acute Coronary Syndrome: a review - Candra; Atyanti Isworo; Arif Setyo Upoyo (Journal of Bionursing, 2021)
Background. Patients with acute coronary syndrome have many compalints such as: chest pain, anxiety, and stress. The management of these symotoms can be pharmacological and non-pharmacological therapy. One of non-pharmachological therapy that can be applied in acute coronary syndrome pastient is massage therapy. Massage therapy is an intervention that is easy to use, safe and inexpensive. Methods. This study was conducted to reviews articles regarding massage therapy on chest pain, anxiety, and stress in patients with acute coronary syndrome. The literature search was carried out through the Google scholar, ScienceDirect, Pubmed and Proquest databases which the inclusion criteria were article in English from 2017 to 2012, an experiment research design. The search used keywords, namely “reflexotherapy” OR “hand and foot massage” AND “chest pain” OR “stress OR “anxiety” OR “acute coronary syndrome. Results. There are 6 articles met criteria for analysis, 4 articles have good quality scores, and 2 articles in medium value. The articles shows the effectiveness of massage therapy on chest pain, anxiety and stress in patients with acute coronary syndrome. Conclusion. Massage therapy effectiveness to reduce chest pain, anxiety, and stress in patients with acute coronary syndrome.